Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

By definition, as set $E$ is measurable if for any set $C$ $$\mu^\ast(C) = \mu^\ast(C\cap E) + \mu^\ast(C \cap E^c).$$

Is it true that if either $A$ or $B$ is measurable, then we can't have

$$ \mu^\ast(A\cup B) \lt \mu^\ast(A) + \mu^\ast(B)?$$

Please if it is true can you offer a proof? I've tried but failed.

share|cite|improve this question
Take a non-measurable subset $B$ of a measurable set $A$... Or even easier, let $A = B$ be of positive outer measure. – t.b. Mar 30 '12 at 19:23
Of course it's possible: take $A=[0,1]$ and $B=[0.5,1.5]$. Then $\mu^*(A\cup B) = 1.5$, $\mu^*(A)=1$, and $\mu^*(B)=1$. – Arturo Magidin Mar 30 '12 at 19:28
@ArturoMagidin: So the claim is false... – Dave Mar 30 '12 at 19:34
@Dave: Yes, it's quite false. Or as t.b. suggested, any measurable $A$ of nonzero outer measure will give an example that the strict inequality can indeed hold. What made you think it couldn't? – Arturo Magidin Mar 30 '12 at 19:39
I guess you want the sets to be disjoint. – Michael Greinecker Mar 30 '12 at 19:39
up vote 2 down vote accepted

Without assuming that $A$ and $B$ are disjoint, this is wrong for silly reasons, as was pointed out in the comments: if $A$ has positive (outer) measure and $B$ overlaps with $A$ in a non-trivial way, we always have $\mu^\ast (A \cup B) \lt \mu^\ast (A) + \mu^\ast(B)$. For a specific example, we may take $A = [0,2]$ and $B=[1,2]$ so that $2 = \mu^\ast(A \cup B) \lt 3 = \mu^\ast[0,2]+\mu^\ast[1,2]$ with respect to Lebesgue outer measure.

However, if $A$ is measurable and $B$ is disjoint from it, we can take $C = A \cup B$ and $E = A$ and use Carathéodory's criterion (the definition of measurability you gave) together with $C \cap A = A$ and $C \cap A^c = B$ to see that $$ \mu^\ast (A \cup B) = \mu^\ast(C) = \mu^\ast (C \cap A) + \mu^\ast(C \cap A^c) = \mu^\ast(A) + \mu^\ast(B), $$ which is the desired equality.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.